Konsep Jilbab Masa Klasik-Kontemporer (Studi Komparatif Kitab Tafsir Al-Misbah dan Kitab Tafsīr Al-Kabīr) - Farida Nur ‘Afifah; Siswoyo Aris Munandar (Refleksi: Jurnal Kajian Agama dan Filsafat, 2020)
Hijab is identified with loins and still a discussion of ambiguity. Because the hijab from time to time has a narrowing of meaning. The issue was increasingly margined and raised to the international world after the French Government planned, and had even established restrictions on the use of religious symbols in French schools. One of them is the use of hijab which is said to be symbol of Islam. This article will discuss the hijab, including the views of middle-classical interpretations of scholars such as Ibn Taymiyah and contemporary interpretations of scholars such as M. Quraish Shihab. Here some views on the headscarves according to previous scholars seem too strict, with contemporary scholars being better known for their concessions in responding to contemporary problems. After that will be seen its relevance to the present.